The Effect of Internship Quality, Professional Competence, and Career Orientation on The Work Readiness of Internship Participants at State-Owned Enterprises in Surabaya - Amanda Nur Azzahra; Budi Prabowo (Jurnal Bisnis dan Manajemen, 2026)
This study examines how internship quality, professional competence, and career orientation shape the work readiness of interns within State-Owned Enterprises (SOEs) in Surabaya. The emergence of a competency gap and high rates of educated unemployment serve as the underlying urgency for this study, necessitating mature work readiness through quality internship experiences, professional competence mastery, and directed career orientation. This study is categorized as associative research using a quantitative approach. Adopting a quantitative-associative approach, the study utilized the Cochran formula to determine a representative sample of 196 participants, identified through purposive sampling Statistical evaluations were performed using a multiple linear regression model via SPSS version 26. The research findings confirm that internship quality, professional competence, and career orientation simultaneously exert a significant positive influence on work readiness. Furthermore, partial analysis reveals that each of these three factors contributes significantly and positively to the development of work readiness among SOEs interns in Surabaya. The coefficient of determination (R2) value of 50.4% indicates that the variation in work readiness can be explained by these three variables, while the remaining 49.6% is explained by other factors outside this research model. The implication of this study is that the management of SOEs in Surabaya needs to prioritize improving the quality of mentoring, honing technical competencies, and strengthening the career direction of interns as primary strategies for producing a job-ready workforce.